Bungo stray dogs. 06 - Asagiri, Kafka (Bungo stray dogs, 2018)
"Ryuunousuke Akutagawa pits his Rashomon against Nathaniel Hawthorne's The Scarlet Letter as the war between the Armed Detective Agency, the Guild, and the Port Mafia escalates. While each side tries to outwit and outflank the other, Chuuya Nakahara suddenly appears, ready to make a deal with the Agency. Can Nakahara's 'diplomacy' be trusted, or will he lead the Agency into even greater peril...?"--Page [4] of cover.